Kinerja Dinas Sosial dalam Menurunkan Angka Penyandang Masalah Kesejahteraan Sosial (PMKS) Bagi Lanjut Usia Terlantar di Kota Jambi Provinsi Jam - marlina, lina; Arliyanti, Bella (Jurnal Konstituen, 2024)
The number of displaced elderly people in Jambi City is still quite high so this research has an urgency to examine the performance of social services in dealing with these problems. The purpose of this study was to determine and analyze the performance of social services in reducing the number of Persons with Social Welfare Problems (PMKS) for neglected elderly in Jambi City, Jambi Province. The purpose of this study is to determine and analyze the performance of the Social Service in reducing the number of Persons with Social Welfare Problems (PMKS) for the Neglected Elderly in Jambi City. The research method employed was qualitative. The results show that the Jambi City Social Service shows varying aspects of productivity, with challenges in HR competence and implementation of training programs, while facilities and infrastructure are considered good. The service quality aspect of the Jambi City Social Service is classified as good, with punctuality and adequate attitude of officers, although there are challenges in the comfort of the place and certainty of costs. The responsiveness aspect of the Jambi City Social Service in meeting community needs is quite good, but there are obstacles to community satisfaction related to the availability of assistance and the fulfillment of complaint reports. The internal supervision of the Jambi City Social Service is considered quite effective with good coordination with various related parties to deal with the Displaced Elderly. In conclusion, the Performance of the Social Service in Reducing the Number of Persons with Social Welfare Problems (PMKS) for the Neglected Elderly in Jambi City, Jambi Province is quite good. Keywords: Performance, Social Welfare, People with Social Welfare Problems